2016
DOI: 10.1186/s12920-016-0234-1
|View full text |Cite
|
Sign up to set email alerts
|

“A rising tide lifts all boats”: establishing a multidisciplinary genomic tumor board for breast cancer patients with advanced disease

Abstract: Background: Research suggests that multidisciplinary genomic tumor boards (MGTB) can inform cancer patient care, though little is known about factors influencing how MGTBs interpret genomic test results, make recommendations, and perceive the utility of this approach. This study's objective was to observe, describe, and assess the establishment of the Breast Multidisciplinary Genomic Tumor Board, the first MGTB focused on interpreting genomic test results for breast cancer patients with advanced disease. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Of note, all clinicians who referred a patient to this sequencing study were invited to attend a Precision Medicine Tumor Board, consisting of a multidisciplinary team of oncologists, molecular and clinical geneticists, genetic counselors, bioinformaticians, pathologists, and bioethicists (Everett et al 2014). Other centers have also begun to develop similar precision medicine-focused tumor boards to specifically review tumor testing results (Gunderson et al 2016; McGowan et al 2016; Schwaederle et al 2014). These types of multidisciplinary conferences may present another opportunity for clinicians to increase their education about tumor testing and increase direct interactions between basic scientists and clinicians, which could aid in improved communication and alignment in the perceived goals and outcomes of tumor testing.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, all clinicians who referred a patient to this sequencing study were invited to attend a Precision Medicine Tumor Board, consisting of a multidisciplinary team of oncologists, molecular and clinical geneticists, genetic counselors, bioinformaticians, pathologists, and bioethicists (Everett et al 2014). Other centers have also begun to develop similar precision medicine-focused tumor boards to specifically review tumor testing results (Gunderson et al 2016; McGowan et al 2016; Schwaederle et al 2014). These types of multidisciplinary conferences may present another opportunity for clinicians to increase their education about tumor testing and increase direct interactions between basic scientists and clinicians, which could aid in improved communication and alignment in the perceived goals and outcomes of tumor testing.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in work practices were typical of a "learning organization", and reflected the ability to account for each situation, thereby improving organizational effectiveness. Paradoxically, the MTB members who participated in our study, like those involved in other MTBs in the literature, advocated a global standardization of responses and procedures at all levels [7,8,29,32], highlighting a tension between procedure stabilization and learning dynamics. Edmonson's framework showed us, that at an organizational level, procedures can be stabilized without limiting practice flexibility [30].…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review showed that MTBs were diverse, ranging from small advisory boards providing treatment recommendations, to boards incorporated into large precision oncology-based clinical trials; all differed in composition, expert categories, genomic areas, bioinformatics techniques and workflows [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Our criticism of the notion of trading zones also applies, mutatis mutandis , to contributions that have analysed MTBs in terms of a ‘pooling [of] professional expertise’ (McGowan et al . : 6). By merely focusing on the presence of different experts (albeit acknowledging the fact that new, nonclinical specialists have joined the fray), and even when emphasising ‘transdisciplinary engagement’ rather than mere multidisciplinarily (Knepper et al .…”
Section: Investigating Mtbs: Conceptual Musingsmentioning
confidence: 95%